Prevalencia de pacientes politraumatizados por accidentes de tránsito en el área de emergencia en el hospital Julius Doefpner de Zamora. Año 2015 - Montaño Torres, Monica Lucia (2016)
The purpose of this study was to determine the prevalence of trauma patients by traffic accidents in the area Hospital Emergency Julius Doepfner City Zamora in the period from January to July 2015. To fulfill observational study was conducted retrospective, descriptive, and bibliographic cross. The observation technique was used by a data collection guide multiple trauma patients seen. From the data obtained could be determined 24.84%, corresponding to group 21 to 30 years, followed by those 16 to 20 years with 22.98%, with 21.12%, are 31 to 40 years; predominantly male with 79.50%, mixed race ethnicity predominated with 95.03%, 59.63% are the residents of the city of Zamora. The most significant lesions in patients were: 62.11% tips; Traumatic Brain 34.16%; 49.69% of the vehicles are followed with 36.65% of motorcycles, 62.11% were referred to home. As a contribution to reduce the problem described an awareness campaign aimed at drivers and pedestrians in the city of Zamora was executed. It is concluded that the prevalence of multiple injuries is 39.66% being the trauma of the extremities caused by vehicles are the most relevant with 62.11%.